Development of Nanocrystal Compressed Minitablets for Chronotherapeutic Drug Delivery - Nagaraja Sreeharsha; Nimbagal Raghavendra Naveen; Posina Anitha; Prakash S. Goudanavar; Sundarapandian Ramkanth; Santosh Fattepur; Mallikarjun Telsang; Mohammed Habeebuddin; Md. Khalid Answer (MDPI AG, 2022)
The present work aimed to develop a chronotherapeutic system of valsartan (VS) using nanocrystal formulation to improve dissolution. VS nanocrystals (VS-NC) were fabricated using modified anti-solvent precipitation by employing a Box-Behnken design to optimize various process variables. Based on the desirability approach, a formulation containing 2.5% poloxamer, a freezing temperature of −25 °C, and 24 h of freeze-drying time can fulfill the optimized formulation's requirements to result in a particle size of 219.68 nm, 0.201 polydispersity index, and zeta potential of −38.26 mV. Optimized VS-NC formulation was compressed (VNM) and coated subsequently with ethyl cellulose and HPMC E 5. At the same time, fast dissolving tablets of VS were designed, and the best formulation was loaded with VNM into a capsule size 1 (average fill weight-400-500 mg, lock length-19.30 mm, external diameter: Cap-6.91 mm; Body-6.63 mm). The final tab in cap (tablet-in-capsule) system was studied for in vitro dissolution profile to confirm the chronotherapeutic release of VS. As required, a bi-pulse release of VS was identified with a lag time of 5 h. The accelerated stability studies confirmed no significant changes in the dissolution profiles of the tab in cap system (f2 similarity profile: >90). To conclude, the tab in cap system was successfully developed to induce a dual pulsatile release, which will ensure bedtime dosing with release after a lag-time to match with early morning circadian spikes.